Retenční nádrže a stoky na stokové síti - Kolář, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Tato bakalářská práce je zaměřena na navrhování, provozování a řízení retenčních nádrží a retenčních stok na stokových sítích. Je zde zmíněn jejich účel, funkce a využití, jejich rozdělení, stavební řešení, konstrukce a jejich vybavení. Dále jsou uvedeny dva konkrétní příklady retenčních nádrží v Brně a krátké shrnutí počtů retenčních nádrží ve vybraných českých městech. Součástí práce je modelový příklad výpočtu objemu retenční nádrže a retenční stoky pro obec Horní Lapač.

This thesis is focused on the design, operation and management of retention basins and retention sewers to sewerage networks. There is also mentioned their purpose, function and use, their distribution, building design, construction and equipment. Below are two specific examples of retention reservoirs in Brno and short summary of number of retention ponds in selected Czech cities. Part of the work is a model example of calculating the amount of retention basins and retention ditches for the village of Horní Lapač.
Retention basins and sewers on the sewer network
Keywords: retenční nádrž; retenční stoky; retence srážkových vod; provoz nádrží; retention basins; retention sewer; retention of rainwater; operation of reservoirs